Psittophagus hollandicus n. sp., a new feather mite species (Acariformes: Pterolichidae) from the cockatiel Nymphicus hollandicus (Kerr, 1792) (Psittaciformes: Cacatuidae) in Brazil - Hernandes, Fabio Akashi [UNESP] (Acarologia-universite Paul Valery, 2017)
A new feather mite species, Psittophagus hollandicus n. sp. (Acariformes: Pterolichidae), is described from the cockatiel Nymphicus hollandicus (Kerr, 1792) (Psittaciformes: Cacatuidae) kept in captivity in Brazil.
Keywords: Acari; Psoroptidia; Pterolichoidea; systematics; household pets